Challenges In Teaching English Vocabulary To Special Needs Students Through Technology - Hidayat, Nur; Jannah, Sheilla Marfuatul (Jetlal, 2025)
The development of digital technology in recent decades has influenced English education, especially in teaching vocabulary. Several previous studies have been investigated that focus on teaching vocabulary challenges through technology. However, all of those studies do not touch on the use of technology in special needs students. This study investigated the teachers’ challenges in developing students with special needs through technology. A qualitative approach with a case study design was used in this study. This study involved six EFL female teachers who taught students with special needs in one of the inclusive schools in Central Java, Indonesia, with several criteria, including having at least five years of experience in learning by using technology for teaching children with special needs, one of which is in the context of teaching vocabulary to students with special needs themselves. A semi-structured interview was designed to collect the data to obtain detailed information about teachers' barriers to using technology to develop students with special needs vocabulary. Thematic analysis was conducted to analyze the qualitative data in some steps: transcription of the interviews, identification of the main themes, coding, categorizing the themes, and making a conclusion. The study's findings indicated that teachers faced three main challenges: students’ concentration, engagement, and language.